Away from the edges: a new Solutrean site in interior Iberia. Foz do Medal Left Bank, Sabor Valley, Northeast Portugal (NW Iberia) - Gaspar, Rita (2018)
Submitted by Mário Reis (marioreis@arte-coa.pt) on 2018-08-27T11:14:47Z No. of bitstreams: 1 Gasparetal2015a - Away.pdf: 557998 bytes, checksum: 941ea1730a5e81369deb89f792abeda3 (MD5)